AB0446 Physician-reported behaviours and treatment trends of tumour necrosis factor inhibitor use: cycling versus switching in five european countries: france, germany, italy, spain and the uk. (12th June 2018) - Curtis, J.R.; Sullivan, E.; Kershaw, J.; Blackburn, S.; Mahajan, P.; Boklage, S.
Abstract : Background: Previously, most biologics prescribed for treating rheumatoid arthritis (RA) were tumour necrosis factor inhibitors (TNFi) and it was common practice to prescribe a second TNFi after failure of the first. Biologics with different mechanisms of action (MOA) have become available and 2016 European League Against Rheumatism guidelines recommend cycling to another TNFi or switching to a biologic with a new MOA following failure of the first TNFi. Objectives: Describe the proportion of patients in 5 EU countries who, after failure of a first TNFi, cycle to a second TNFi ('TNFi cycling') vs switch to a treatment with a different MOA ('Switch'), and identify patient characteristics and physician attitudes associated with TNFi cycling vs switching. Methods: Data were from the Adelphi Disease Specific Programme (DSP), a cross-sectional survey conducted in 2017 in France, Germany, Italy, Spain and the UK. Rheumatologists prospectively completed records about the next 10 patients with RA who consulted them during the study period; records captured treatment history and clinical details. Patients were included in the analysis if they had been prescribed at least 2 different biologics, their first was a TNFi and their second was known. Patients were assigned to 2 cohorts: 'TNFi cycling' patients received a TNFi at first- and a different TNFi at second-line; 'Switch' patients received a TNFi at first-line and a non-TNFi at second-line. Bi-variate comparisons of groups were conducted using nonparametric tests as appropriate. Results: All physicians in the DSP sample (n=301) were questioned on their beliefs around TNFis; 86.4% believed that there is a class effect with TNFis regarding efficacy and/or safety (table 1). Data from 359 patients were included in the analysis (75.8% female; mean [SD] age 56.5 [12.7]), of whom 167 (46.5%) were TNFi cycling, and 192 (53.5%) were Switch patients (female: 70.7% vs 80.2%, respectively; p=0.04; age: 55.8 [13.1] vs 57.1 [12.4], respectively; p=0.42). The most common reasons for discontinuing first-line therapy among the TNFi cycling and Switch cohorts were worsening condition (36.3% vs 45.3%, respectively; p=0.13) and loss of efficacy (48.9% vs 48.3%, respectively; p=1.0). Prior to the second biologic, patients in the TNFi cycling cohort spent a numerically longer amount of time on first-line therapy vs the Switch cohort (2.0 [2.2] years vs 1.7 [1.9] years; p=0.35), and had a longer disease duration at the time of initiation of second-line non-TNFi (7.3 [6.6] years vs 6.6 [7.8] years; p=0.15). Conclusions: Despite evidence from literature suggesting that RA patients have a better treatment response switching to a non-TNFi after initial TNFi inadequate response 1 and despite the majority of physicians in our study believing that there is a class effect with TNFis, regarding efficacy and safety, 46.5% of patients still cycled to a second TNFi rather than switched to a non-TNFi as second-line therapy. Reference: [1] Singh, et al. Arthritis Rheumatol2016;68:1–26. Acknowledgements: Research sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: J. Curtis Consultant for: Sanofi and Regeneron Pharmaceuticals, Inc., E. Sullivan Grant/research support from: Sanofi and Regeneron Pharmaceuticals, Inc., J. Kershaw Grant/research support from: Sanofi and Regeneron Pharmaceuticals, Inc., S. Blackburn Grant/research support from: Sanofi and Regeneron Pharmaceuticals, Inc., P. Mahajan Shareholder of: Sanofi, Employee of: Sanofi, S. Boklage Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc.